Test–Retest Reliability of Behavioral Assays of Feedforward and Feedback Auditory–Motor Control of Voice and Articulation. - Kapsner-Smith, Mara R.; Abur, Defne; Eadie, Tanya L.; Stepp, Cara E. (Journal of Speech, Language & Hearing Research, 2024)
Purpose: Behavioral assays of feedforward and feedback auditory–motor control of voice and articulation frequently are used to make inferences about underlying neural mechanisms and to study speech development and disorders. However, no studies have examined the test–retest reliability of such measures, which is critical for rigorous study of auditory–motor control. Thus, the purpose of the present study was to assess the reliability of assays of feedforward and feedback control in voice versus articulation domains. Method: Twenty-eight participants (14 cisgender women, 12 cisgender men, one transgender man, one transmasculine/nonbinary) who denied any history of speech, hearing, or neurological impairment were measured for responses to predictable versus unexpected auditory feedback perturbations of vocal (fundamental frequency, f) and articulatory (first formant, F) acoustic parameters twice, with 3–6 weeks between sessions. Reliability was measured with intraclass correlations. Results: Opposite patterns of reliability were observed for f and F; f reflexive responses showed good reliability and f adaptive responses showed poor reliability, whereas F reflexive responses showed poor reliability and F adaptive responses showed moderate reliability. However, a criterion-referenced categorical measurement of f adaptive responses as typical versus atypical showed substantial test–retest agreement. Conclusions: Individual responses to some behavioral assays of auditory–motor control of speech should be interpreted with caution, which has implications for several fields of research. Additional research is needed to establish reliable criterion-referenced measures of F adaptive responses as well as f and F reflexive responses. Furthermore, the opposite patterns of test–retest reliability observed for voice versus articulation add to growing evidence for differences in underlying neural control mechanisms.